Clinical application of the anterolateral thigh free flap in high energy injuries of the lower extremity - Ignacio, Del Carmen-Ortega; Ignacio, Cahuana-Quispe Alberto; Michel, Jaimes-Duran Edwing; Enrique, Soulé-Martínez Christian (International Journal of Research in Medical Sciences, 2021)
One of the recurring problems in plastic and reconstructive surgery is the loss of tissues of the lower extremities as a result of high-energy injuries. The difficulty of this reconstruction lies in the need for a sufficiently suitable and resistant tissue to allow this restoration. The thigh-free anterolateral flap, since its description in 1984, has great versatility for complex or extensive lower extremity reconstructions. We presented the case of a 37-year-old male patient who had a high-energy road accident on a bicycle, impacting a moving vehicle causing a multi fragmented fracture of the right proximal tibia AO 41 C2.2/Schatzker V. He was treated surgically with material from osteosynthesis and iliac crest graft. It is complicated by infection of the surgical wound, exposure of osteosynthesis material and absence of skin covering. Reconstruction of the upper third of the right leg was performed with a thigh-free anterolateral free flap with 2 end-to-end venous anastomoses from the flap to anterior tibial veins, and 1 end-to-end anastomosis from perforating artery to anterior tibial artery, with no associated complications. The thigh-free anterolateral free flap is a versatile and reliable mechanism for the reconstructive surgeon, as it provides excellent coverage for complex lower extremity wounds as well as low donor site morbidity. Outpatient follow-up with adequate clinical evolution was done.